A population-based study examining the emergence of community-associated methicillin-resistant Staphylococcus aureus USA300 in New York City - Panwar Monica; Trehan Manoj; Gupta Jyoti; Landman David; Bratu Simona; Quale John (BMC, 2006)
Abstract Background Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) is a serious pathogen in several regions in the United States. It is unclear which populations are at high risk for the emergence of these strains. Methods All unique patient isolates of S. aureus were collected from hospitals in Brooklyn, NY over a three-month period. Isolates of MRSA that were susceptible to clindamycin underwent SCCmec typing. Isolates with the SCCmec type IV (characteristic of CA-MRSA strains) underwent ribotyping. Demographic information involving the neighborhoods of Brooklyn was also gathered and correlated with the prevalence of CA-MRSA strains. Results Of 1316 isolates collected during the surveillance, 217 were MRSA susceptible to clindamycin. A total of 125 isolates possessed SCCmec type IV; 72 belonged to the USA300 strain and five belonged to the USA400 strain. Hospitals in the eastern part of the city had the highest prevalence of USA300 strain. Individuals in the eastern region, when compared to the western region, were more likely to be Black, Hispanic, female, and < 18 years of age, and to have households of ≥ 3 persons. In addition, the median household income was lower, and the proportion of individuals on public assistance was higher, for the population in the eastern region. Conclusion The USA300 strain of CA-MRSA is emerging in New York City. In this population-based study, urban regions of lower socioeconomic status and with evidence of overcrowding appear to be at higher risk for the emergence of this pathogen.